STUDY ON FACTORS ASSOCIATED WITH TREATMENT ADHERENCE AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS (Vietnam Journal of Community Medicine, 2026)
Objective: Study aimed to assess the level of treatment adherence and identify associated factors among outpatients with type 2 diabetes mellitus.Subjects and methods: A cross-sectional descriptive study was conducted on 332 outpatients with type 2 diabetes mellitus from March to September 2025. Data were collected through structured interviews using a standardized questionnaire and medical records. Multivariate logistic regression analysis was performed to identify factors associated with treatment adherence, with a significance level set at p < 0.05.Results: The overall treatment adherence rate was 50.6%. Among adherence components, 90.1% adhered to medication, 97.9% regularly monitored blood glucose, 88% maintained physical activity, and 59.9% followed dietary recommendations. Statistically significant factors associated with adherence included education level ≥ high school (OR = 2.45; p = 0.013), dyslipidemia (OR = 1.83; p = 0.039), disease duration > 5 years (OR = 0.62; p = 0.047), good fasting blood glucose control (OR = 2.97; p < 0.001), and good HbA1c control (OR = 3.21; p < 0.001).Conclusion: Patients with type 2 diabetes mellitus demonstrated relatively good adherence, particularly regarding medication use and blood glucose monitoring. Higher education level, shorter disease duration, and good glycemic control were strong predictors of better adherence. Strengthening health education, personalized counseling, and long-term management programs is essential to improve treatment outcomes in patients with type 2 diabetes mellitus.
Keywords: Type 2 diabetes mellitus, treatment adherence, associated factors, glycemic control.